Severity of obstructive sleep apnea and its impact on coronary artery disease outcomes: A cross-sectional study in Egypt - Hossam Eldin M. Mahmoud; Ahmed Hussein; Esraa A. Taha; Eptehal M. Dongol; Ahmed G. Bakry (Heart Vessels and Transplantation)
Objectives: Coronary artery disease (CAD) and obstructive sleep apnea (OSA) share mechanisms such as intermittent hypoxia, inflammation, and sympathetic activation, worsening cardiac function and CAD severity. This study aimed to assess OSA prevalence in CAD patients and its relationship to CAD severity and cardiac function, while evaluating the diagnostic performance of the STOP-BANG questionnaire.